Deepseek Adoption as a Companion to Support SMEs' Digital Marketing Strategy in Surabaya - Desy Candra Novitasari (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Purpose: This study aims to analyze the factors influencing the behavioral intention to adopt Deepseek as a digital marketing companion among Small and Medium Enterprise (SME) actors in Surabaya. The hypotheses tested include the influence of Perceived Ease of Use (PEU) and Perceived Usefulness (PU) on Behavioral Intention (BI) to adopt. Methods: This quantitative research employs a PLS-SEM model approach. Data was collected through an online questionnaire from 150 respondents comprising owners, marketing managers, or related staff across various SME sectors in Surabaya. The research instrument refers to validated variables of PEU, PU, and BI. Data analysis includes reliability and validity tests, as well as hypothesis testing using path analysis. Results: The findings indicate that both Perceived Ease of Use and Perceived Usefulness significantly and positively affect the intention to adopt Deepseek. Perceived Ease of Use also shows a strong direct effect on Perceived Usefulness. The model explains 87.3% of the variance in Behavioral Intention. Implications: The results provide practical insights for AI developers like Deepseek to enhance features that emphasize usability and tangible benefits for specific business tasks. For SME stakeholders and policymakers, the study highlights key drivers for digital tool adoption, suggesting that training programs should focus on improving both the perceived ease and the practical utility of such technologies to accelerate digital transformation in the SME sector.